Café Desvelado: un cortometraje como ventana al cine de la diversidad - Castillo Valdivia, Pamela Alessandra (2021)
‘Café Desvelado’ is a fiction short film that explores the relationship of a nonheterosexual couple in view of a possible breakup. This thesis develops film production from different stages and manages to be exhibited at world-wide festivals. Consequently, it is shown that an audiovisual product, together with the appropriate distribution mechanisms, generates exhibition spaces and promotes dialogue on current issues, such as sexual diversity.